Silica-Polymer Ionogel for Energy Storage Applications - Raquel San Emeterio; Antía Santiago-Alonso; Pablo Vallet; María Villanueva; Josefa Salgado; Juan José Parajó (Chemistry Proceedings, 2024)
Ionic Liquids (ILs) are composed of ions, usually an organic cation with an organic or inorganic anion, with a melting point below 100 °C and in most cases below room temperature. These compounds exhibit important and characteristic properties such as high ionic conductivity, good thermal and electrochemical stability and low toxicity and flammability. Subsequently, ILs have been studied as promising substitutes for conventional electrolytes for electrochemical applications, both as bulk liquids or confined in polymer matrices, commonly known as ionogels, which have the advantages of not leaking and enhancing safety and manipulation during device assembly. For this work, the ionogel of the IL 1-Ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2C1Im][TFSI]) was synthesized by the polymerization of Tetramethyl orthosilicate (TMOS) and Dimethyldimethoxysilane (DMDMS). Thermal analyses of the pure ionic liquid and electrochemical response of the ionogel were studied in comparison with the corresponding bulk IL by using differential scanning calorimetry (DSC), thermogravimetry (TGA) and broad-band dielectric spectroscopy (BBDS), respectively.